Search for electroweak production of supersymmetric particles in final states with two τ-leptons in √s = 13 TeV pp collisions with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; et al. (Journal of high energy physics, 2024)
Three searches for the direct production of τ-sleptons or charginos and neutralinos in final states with at least two hadronically decaying τ-leptons are presented. For chargino and neutralino production, decays via intermediate τ-sleptons or W and h bosons are considered. The analysis uses a dataset of pp collisions corresponding to an integrated luminosity of 139 fb−1, recorded with the ATLAS detector at the Large Hadron Collider at a centre-of-mass energy of 13 TeV. No significant deviation from the expected Standard Model background is observed and supersymmetric particle mass limits at 95% confidence level are obtained in simplified models. For direct production of $$ {\overset{\sim }{χ}}_1^{+}{\overset{\sim }{χ}}_1^{-} $$, chargino masses are excluded up to 970 GeV, while $$ {\overset{\sim }{χ}}_1^{± } $$and $$ {\overset{\sim }{χ}}_2^0 $$masses up to 1160 GeV (330 GeV) are excluded for $$ {\overset{\sim }{χ}}_1^{± }{\overset{\sim }{χ}}_2^0/{\overset{\sim }{χ}}_1^{+}{\overset{\sim }{χ}}_1^{-} $$production with subsequent decays via τ-sleptons (W and h bosons). Masses of τ-sleptons up to 500 GeV are excluded for mass degenerate $$ {\overset{\sim }{τ}}_{L,R} $$scenarios and up to 425 GeV for $$ {\overset{\sim }{τ}}_L $$-only scenarios. Sensitivity to $$ {\overset{\sim }{τ}}_R $$-only scenarios from the ATLAS experiment is presented here for the first time, with $$ {\overset{\sim }{τ}}_R $$masses excluded up to 350 GeV.
The ATLAS collaboration: G. Aad, L.M. Baltes, F. Bartels, M.M.Czurylo, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, M. Klassen, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, F. del Rio, S. Rodriguez Bosca, C. Sauer, A. Schoening, H.-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser [und 2902 weitere Personen]
Gesehen am 25.08.2025
Im Titel steht der Buchstabe "s" unter dem Wurzelsymbol